2019
DOI: 10.3390/rs11192298
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Deformation along Railway Systems Combining Multi-Temporal InSAR and LiDAR Data

Abstract: Multi-temporal interferometric synthetic aperture radar (MT-InSAR) can be applied to monitor the structural health of infrastructure such as railways, bridges, and highways. However, for the successful interpretation of the observed deformation within a structure, or between structures, it is imperative to associate a radar scatterer unambiguously with an actual physical object. Unfortunately, the limited positioning accuracy of the radar scatterers hampers this attribution, which limits the applicability of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 34 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…For instance, Ref. [ 28 ] obtained an association of 94% PS by customizing the significance level to 5%, for the high-resolution Radarsat-2 (Extra Fine mode) SAR data. At the end, 3259 PS out of 3328 were geometrically associated with the real objects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Ref. [ 28 ] obtained an association of 94% PS by customizing the significance level to 5%, for the high-resolution Radarsat-2 (Extra Fine mode) SAR data. At the end, 3259 PS out of 3328 were geometrically associated with the real objects.…”
Section: Resultsmentioning
confidence: 99%
“…Reference [ 27 ] showed for medium resolution SAR data such as Sentinel-1 a/b, 2-D positioning could be improved, ranging between decimeter and couple of meters, with CRs. In addition, [ 28 ] showed that using laser scanning data (LiDAR, e.g., AHN3), the Radarsat-2 (Extra Fine mode) derived PS geolocation along a railway line can be improved. This study will further test and evaluate the Sentinel-1 derived PS geolocation improvement aided by laser scanning data.…”
Section: Introductionmentioning
confidence: 99%
“…GPR information can also complement other non-destructive load tests, such as a stiffness assessment with a rolling stiffness measurement vehicle [290], a falling weight deflectometer (FWD) [95] and a light FWD [17,95,286,291], a dynamic cone penetrometer [90], a geo endoscopy test [90], [292] and light detection and ranging or laser imaging detection and ranging (LiDAR) [293]. The use of a multi-temporal InSAR (interferometric synthetic aperture radar) for transport infrastructure monitoring has also been significantly increasing during the last few years [294][295][296]. Studies undertaken on railways have shown the potential of the applicability of In-SAR together with GPR, mainly for the detection of causes of track subsidence [297], and to monitor subsidence at the transition zones of railway bridges [298].…”
Section: Railways Inspectionmentioning
confidence: 99%
“…To overcome these limitations of classical DInSAR, various multi-temporal InSAR (MTInSAR) approaches have been developed over the last two decades (Ciampalini et al, 2019;F. Hu et al, 2019;Sousa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%